Membrane fluidity of RBL-2h3 cells treated with insulin and BMOV using time-correlated single photon counting fluorescence anisotropy - Roan, Chelsea Rene' Lenne, author; Roess, Deborah A., advisor; Barisas, B. George, advisor; Crans, Debbie C., committee member (Colorado State University. Libraries, 2013)
Transition metal compounds have been shown to be insulin-enhancing but the mechanism of action has not been fully elucidated. With obesity, diabetes and other metabolic derangements increasing in developed countries, understanding the effects these compounds will better target drug therapy. Previous investigations have focused on vanadium and have studied the effects on protein-protein interactions in the insulin signaling pathway. In this paper, we propose that the mechanism of action may also include interactions with the plasma membrane. Lipids as bioactive molecules are on the horizon as the next great area of exploration in biochemistry and molecular biology. Within the insulin signaling pathway, the insulin receptor functions optimally in areas of specialized lipid packing that are characterized as small detergent insoluble regions enriched in sphingomyelin and cholesterol and termed lipid rafts. These lipid rafts are a subset of microdomains within the plasma membrane. Obesity and excess lipids have been shown to increase inflammation via increases in free fatty acids, cytokines, TNF-α, and reactive oxygen species resulting in the peroxidation of membrane lipids. We propose that one cause of insulin resistance, a failure of insulin receptors to respond to insulin, is due to disruption of the membrane lipids resulting in an increase in membrane fluidity. This disruption results in displacement of insulin receptors out of specialized lipid rafts. We propose that treatment with vanadium will result in an increase in membrane rigidity favoring lipid raft formation and restoration of insulin receptors to a platform favoring optimal signaling. Time-correlated single photon counting fluorescence anisotropy was used to measure the membrane fluidity of RBL-2H3 cells treated with insulin and the vanadium compound bis(maltolato)oxovanadium(IV) (BMOV).
Keywords: BMOV; anisotropy; fluidity; insulin; membrane; signaling